Pengaruh Kelengkapan Sumber Belajar Dan Kedisiplinan Terhadap Prestasi Belajar Siswa Kelas 5 SD Negeri Kalongan 1 Kecamatan Purwodadi Kabupaten Grobogan Tahun Ajaran 2015/2016 - Rahmawati, Farida, Drs. Saring Marsudi, SH. M.Pd (2016)
The purpose of this study was to determine include: 1) Effect of completeness of learning resources on student achievement in grade 5 in elementary school in the academic year 2015/2016 Kalongan 1, 2) Effect of discipline on student achievement in grade 5 at Elementary School Kalongan 1 academic year 2015 / 2016, 3) Effect of completeness and discipline of learning resources on student achievement in grade 5 at Elementary school Kalongan 1 of the school year 2015/2016. This type of research is based on a quantitative approach to the type of research Ex-Post Facto. The analysis technique used is multiple linear regression, t test, Test F. Based on the analysis of data: 1) equation regression coefficient obtained Y = 39,339+ 0,170X1 + 0.159 X2. 2) Test Results t completeness of learning resources thitung (2, 120)> t table (2.045), the completeness of learning resources have a positive effect on student achievement. 3) disciplinary positive effect on student achievement, it is based on t test results tcount (2, 092)> t table (2.045). 4) The test results f significance value 0.000 <0.05, meaning completeness source of learning and discipline have positive effect on student achievement in fifth class at Elementary School Kalongan 1 Purwodadi Grobogan of academic year 2015/2016.